2022
DOI: 10.7759/cureus.28907
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Malignant Pleural Effusion Secondary to Endometrial Cancer After One Year of Hysterectomy

Abstract: Endometrial cancer is the most common malignant tumor of the female genital tract. It can rarely metastasize to the lung, presenting as a pulmonary nodule and pleural effusion. Here we present a case of a 76-year-old female with a history of endometrial cancer who underwent a total abdominal hysterectomy and came one year later for evaluation of shortness of breath. She was found to have pleural effusion. Diagnostic and therapeutic thoracentesis was positive for malignant cells originating from endometrial can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…However, arising primarily in post-menopausal women, serous carcinoma of the uterus is very aggressive and has a tendency for early hematogenous and lymphatic spread. It also has a tendency for intraperitoneal spread [ 2 ]. Lung is one of the organs to which endometrial cancer may spread.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, arising primarily in post-menopausal women, serous carcinoma of the uterus is very aggressive and has a tendency for early hematogenous and lymphatic spread. It also has a tendency for intraperitoneal spread [ 2 ]. Lung is one of the organs to which endometrial cancer may spread.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in India found the incidence of pleural effusion among endometrial cancers to be between 6-10% [ 7 , 8 ]. There are isolated case reports in the literature whereby uterine serous carcinoma presents with pleural effusion in the recurrent setting or in the already diagnosed patient [ 1 , 2 ]. There has not been, to our knowledge, previous reports of malignant pleural effusion as the diagnostic presentation of serous endometrial carcinoma in a patient with history of breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations